Inflation and India's Economic Crisis - Rao, V. K. R. V. et al; Institute of Economic Growth (India) (Delhi : Vikas Pub. House, 1973)
The authors have made a number of excellent suggestions for rationalizing price controls, which will curb black money and improve revenue.
At head of title: Institute of Economic Growth, Delhi.
osc 16/06/17
Loans
Keywords: Inflation (Finance); Monetary policy